Strategic economy in Japan - Huber, Thomas M. (Westview Press, 1994)
Contents: Thomas Huber argues in this book that Japan's economy functions more in the manner of a modern military system than a free market economy. He sets out to demystify the Japanese economic "miracle" by uncovering the driving strategy behind it, and shows how institutions, government policy-makers and big business collaborate to plan, direct and implement the working of "Japan Inc", making it a formidable force in world trade.